2011
DOI: 10.1002/crat.201000207
|View full text |Cite
|
Sign up to set email alerts
|

Formation of oxygen deficient BaPbO3‐x by oxalate decomposition

Abstract: BaPbO 3 is assumed to be oxygen deficient but the exact determination has never been reported. The aim of this study is to investigate the correlation between synthetic conditions and the resulting oxygen deficiency of BaPbO 3-x . The formation of BaPbO 3-x by decomposition of barium-and lead oxalate up to 850 °C is significantly faster compared to conventional high temperature solid state reactions of oxide compounds. The discrete reaction steps were studied by simultaneous thermal analysis and X-ray powder d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The same observation has been made by Namtame et al 29 . In fact Franz et al have synthesized the BaPbO 3 with chemical composition BaPbO 2.74 and BaPbO 2.82 38 . The authors also observed that the BaPbO 3 can only be synthesized with vacancies.…”
mentioning
confidence: 99%
“…The same observation has been made by Namtame et al 29 . In fact Franz et al have synthesized the BaPbO 3 with chemical composition BaPbO 2.74 and BaPbO 2.82 38 . The authors also observed that the BaPbO 3 can only be synthesized with vacancies.…”
mentioning
confidence: 99%